(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): How does the green transition affect the labour force in Slovenia? What are the perceptions of key stakeholders (employers, trade unions, employees, university lecturers, researchers, and journalists) regarding changes in competences, values, and work organisation? How do social factors – such as generational differences, economic inequality, and local regulations – shape the understanding and acceptance of the green transition? Purpose: This research sheds light on the social, cultural, and organizational transformations driven by the green transition. The aim is to understand how various stakeholders perceive these changes and how organizations and individuals are adapting to new demands in the labour market. Method: The study is based on a qualitative anthropological analysis of three focus groups involving representatives of NGOs, trade unions, employers, higher education institutions, researchers, workers, and journalists. The discussions focused on identifying key challenges and opportunities of the green transition, with special emphasis on cultural and organizational shifts in the workplace. Organization: The study provides valuable insights for managers and organizations by identifying key challenges and tensions related to the green transition—particularly regulatory uncertainty, workforce upskilling, and the symbolic transformation of work. It offers strategic directions for fostering inclusive and context-sensitive adaptation, especially for SMEs and vulnerable sectors. Society: The findings underscore the importance of embedding sustainability within broader questions of justice, inclusion, and epistemic recognition. A just transition requires not only technological investment but also the redistribution of knowledge, opportunities, and participation across diverse social groups. It invites a deeper societal reflection on the meaning of sustainability, productivity, and work. Originality: This research contributes a novel anthropological perspective to organizational studies, moving beyond technocratic and economic framings. By focusing on everyday interpretations of sustainability and on the cultural-symbolic dimensions of transition, it highlights the need for policies that resonate with lived experiences and social identities. Limitations / further research: The study is based on a limited number of focus groups and is geographically situated in Slovenia, which may constrain generalizability. Future research should explore comparative perspectives across regions and deepen the analysis of intergenerational and gendered dimensions of green transition experiences.